Structural behaviour of continuous solid solution SmCo₁₋xFexO₃ - Kharko, O.V.; Vasylechko, L.O.; Ubizskii, S.B.; Pashuk, A.; Prots, Yu. (Functional Materials, 2014)
Phase and structural behaviour in the SmCoO₃-SmFeO₃ pseudobinary system has been investigated at the ambient conditions in a whole concentration range by means of X-ray powder diffraction technique applied laboratory and synchrotron radiation sources. Series of mixed samarium cobaltites-ferrites SmCo₁₋xFexO₃ was obtained by the solid state reaction in air at 1573 K. Formation of a continuous solid solution SmCo₁₋xFexO₃ with orthorhombic perovskite structure (GdFeO₃ type, space group Pbnm) has been revealed. Crystal structure parameters of the mixed samarium cobaltites-ferrites, as well as nominally pure SmCoO₃ and SmFeO₃ have been established by full profile Rietveld refinement. Based on the analysis of structural parameters, an influence of the cation substitution on the deformation of the orthorhombic perovskite structure in the SmCo₁₋xFexO₃ series has been established.